ANALISIS USER EXPERIENCE (UX) PADA ONLINE FOOD DELIVERY DI JABODETABEK MENGGUNAKAN USER EXPERIENCE QUESTIONNAIRE (UEQ) (Studi Kasus Layanan GoFood dan GrabFood) (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2023)
According to this research, GoFood has a better user experience than GrabFood, as measured by the User experience questionnaire (UEQ) and UEQ Compare Product analysis. The data analysis, which was based on the responses of 290 people from the Jabodetabek region, indicates that GoFood scored higher on the UEQ and UEQ Compare Product analysis scale. The rating intervals for five (5) indicator groups - attractive, perspicuity, efficiency, dependability, and stimulation - were excellent, while the rating for the novelty indicator was good.